Cultural-Psychological Alienation and Its Effect on the Skill of Standing on the Head in Gymnastics among Students of the Faculty of Physical Education and Sports Science - Hzoar Mohammed, Jabbar; Abdul Hadi Hammood, Anwar; Sabah Adai, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Ground movements are the basic rule for skills on all other devices, and these skills are not without difficulties, as the research problem determines that there is a weakness in the orientation towards the skill of standing on the head and whether cultural-psychological alienation is the reason for the weak orientation of the skill or other reasons, and what is the type of relationship between cultural-psychological alienation in the performance of this skill?To achieve the goals of the research, the researcher will arrive at the procedures that it achieves, including identifying levels of cultural-psychological alienation among students of the Faculty of Physical Education and Sports Science, knowledge of the relationship between cultural-psychological alienation and learning the skill of standing on the head, and is there a statistically significant correlation between cultural-psychological alienation? The skill of standing on the head was done by the researcher using the descriptive approach to its suitability to the nature of the problem. The research sample was randomly selected, amounting to 30 students from the second stage/College of Physical Education and Sports Science - University of Qadisiyah, and it was found that there is an unrelated correlation between cultural-psychological alienation and learning the skill of standing on the head.The researcher concluded that the teacher did not use the educational method in an accurate and organized manner, which leads to not attracting the second-stage students towards practicing the skill, and the teacher not using the principle of reinforcement and correcting the errors that may occur during the performance leads to a poor orientation towards the skill of standing on the head, and the researcher recommended the need to use a good method In gymnastics, to explain and understand the skillful technique, the need to use the principle of reinforcement and the need to provide the appropriate educational environment.